(untitled) (Journal of Society of Surgeons of Nepal, 2018)
Introduction: Empyema thoracis is an uncommon complication of childhood pneumonias but a common problem faced by a thoracic surgeon. Its management is still controversial, with a range of treatment options available and evolving gradually towards adoption of video-assisted thoracoscopic surgery (VATS) as the most commonly practiced one. Aim: The aim of this study was to review our experience in pediatric empyema thoracis. Methods: It was a retrospective review of the prospectively recorded data, spanning a period of 18 months in the Department of Cardio-Thoracic and Vascular Surgery in Manmohan Cardio-Thoracic Vascular and Transplant Center. Results: A total of 40 consecutive patients, 29 males and 11 females, aged 15 years or less were operated upon for a diagnosis of empyema thoracis made based on clinical, radiological and laboratory evidence. All of them were referred patients, mostly from pediatricians. VATS was undertaken in 36 of them, the remaining four treated by open approach. Deloculation sufficed in majority (26/40; 65%) of the patients which mostly (23/26; 90%) had either acute or subacute presentation. Decortication was required in 35% (14/40) of the patients. However, all of the patients but one had a successful outcome in terms of lung expansion, sterilization of the pleural cavity and absence of recurrence. There was no operative mortality. Conclusion: Surgical management of pediatric thoracic empyema is feasible and safe with favorable outcome. VATS is gradually becoming the more favored modality of operative management.